Fiscal Policy and Inclusive Growth in Advanced Countries: Their Experience and Implications for Asia - Almas Heshmati; Jungsuk Kim; Donghyun Park (Asian Development Bank (ADB), 2014)
Advanced economies have a significantly longer history of using fiscal policy to tackle inequality and promote inclusive growth than those in developing Asia. Therefore, as developing Asia explores the more active use of fiscal policy for inclusive purposes, it can learn from the experiences of advanced countries. Those experiences clearly suggest that fiscal policy can have a significant effect on inequality which provides some cause for optimism about its equity-promoting potential. Nevertheless, that optimism should be tempered by the different circumstances of advanced versus developing economies along with the need for developing Asia to maintain fiscal sustainability and economic growth.
hdl:11540/4841
Keywords: D31; H20; H50; 330; fiscal policy; inequality; inclusive growth; advanced countries; developing Asia; Finanzpolitik; Wirtschaftswachstum; Verteilungsgerechtigkeit; Industrieländer; Entwicklungsländer; Asien